2019
DOI: 10.1002/advs.201901438
|View full text |Cite|
|
Sign up to set email alerts
|

Realizing Room‐Temperature Resonant Tunnel Magnetoresistance in Cr/Fe/MgAl2O4 Quasi‐Quantum Well Structures

Abstract: The quantum well (QW) realizes new functionalities due to the discrete electronic energy levels formed in the well‐shaped potential. Magnetic tunnel junctions (MTJs) combined with a quasi‐QW structure of Cr/ultrathin‐Fe/MgAl2O4(001)/Fe, in which the Cr quasi‐barrier layer confines Δ 1 up‐spin electrons to the Fe well, are prepared with perfectly lattice‐matched interfaces and atomic layer number control. Resonant peaks are clearly observed in the differential conductance of the MTJs due to the formation of QWs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Spin-dependent resonant tunneling through quantumwell 14,15 and interface 12 states investigated within line (ii) showed that devices are either operative at low temperatures only or involve technically challenging symmetry confinement in a few mono-layers of ferromagnetic material 16 . Other similar 17 approaches providing TMR modulation are also not robust enough to build energy efficient 18 room temperature spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-dependent resonant tunneling through quantumwell 14,15 and interface 12 states investigated within line (ii) showed that devices are either operative at low temperatures only or involve technically challenging symmetry confinement in a few mono-layers of ferromagnetic material 16 . Other similar 17 approaches providing TMR modulation are also not robust enough to build energy efficient 18 room temperature spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, metallic QWs can incorporate the large exchange splitting on d electrons in spin-polarized QW devices [3][4][5][6][7]. In more recent technological advances, spinpolarized d-band QWs were demonstrated in magnetic tunnel junctions (MTJs), where the confinement potential is produced both by band-gap and band-symmetry mismatches [8][9][10][11].…”
mentioning
confidence: 99%
“…A dislocation-free Fe/MgAl 2 O 4 interface can be realized [27,28], which significantly enhances the phase coherence in QW structures [10,11]. We measure the QW-TAMR effect in epitaxial stacks of Cr/Fe/MgAl 2 O 4 , with the geometry and coordinates depicted in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations